Corporate Governance and Accounting Conservatism in Nigerian Quoted Manufacturing Companies - Modupeola Bello, Bilikis (Kashere Journal of Humanities, Management and Social Sciences, 2022)
The study examines the effect of corporate governance on accounting conservatism. Specifically, the study investigates the effect of board size, board independence and board gender diversity on accounting conservatism. This study utilized the more robust longitudinal data design which is seen as a combination of both cross-sectional and time-series design properties. The population of the study are all manufacturing companies quoted on the Nigerian Stock Exchange. The sample size for the study consists of the 30 manufacturing companies quoted on the Nigerian Stock Exchange with complete data for the study period. In this study, secondary data, by way of annual reports and accounts of the companies in Nigeria and some relevant NSE fact books were used to collect data from 2011-2018. The effect of corporate governance structure on accounting conservatism was analysed using panel regression. The Hausman test for both random and fixed models were conducted including an F-test for the FE model to enable us determines which model was better. The findings reveal that the size of the board (BDS) has a negative effect on accounting conservatism, Board independence (BDIND) shows a statistically significant 5% impact on accounting conservatism though with a positive coefficient while Board gender diversity has a positive impact on accounting conservatism and statistically significant at 5%. In the light of the study findings, the study recommends that companies need to structure their boards such that all key interests are represented as this will go a long way to position the board to act in the best interest of all stakeholders whether in the area of timely loss recognition, managing income uncertainty or in the area of minimizing opportunistic behaviour of management via the conservatism umbrella. Secondly, the study recommends the need for more levels of board independence. Independent board members are a key component of effective corporate governance because of the expertise and objectivity that they bring to companies. Thirdly, the study recommends that companies should strive to achieve an appropriate diversity mix.